COBIB.SI: prirast bibliografskih zapisov v letu 2022 / COBIB.SI: increment of bibliographic records in 2022 - Ema Dornik (Organizacija Znanja)
The article presents in detail the data on the annual increment of bibliographic records in 2022 at annual and monthly levels. The analysis includes 171,503 bibliographic records created by 546 cataloguers. In the last quarter of the year, 27.5% of bibliographic records were created. Most records, i.e. 934 records, were created on Tuesday, 29 November 2022. Thursdays are the most productive days in the year. The fewest records were created in August. When referring to the type of records, the multiannual trend continues also in 2022: most records were created for monographs (50.6%) and component parts (40.5 %). The data on records downloaded from other databases and the data on the annual increment of authority records for personal names and for corporate body names in the CONOR.SI database are included. The results show how important the work of cataloguers in the COBISS system is.